Pairwise products of moduli of families of curves on a Riemannian Möbius strip - Okhrimenko, S. A.; Tamrazov, P. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate pairwise products of moduli of families of curves on a Riemannian Möbius strip and obtain estimates for these products. As one of the factors, we consider the modulus of a family of arcs from a broad class of families of this sort (for each of these families, we determine the modulus and extremal metric).